Les mots du Grand Débat national : les réseaux lexicaux des contributions déposées sur trois plateformes - Sabine Ploux; Michael Genay; Leu Ploux-Chillès (Humanités Numériques)
During the Grand Débat national, launched on January 15, 2019, several platforms such as the Grand Débat national (GDN), Le Vrai Débat (VD), or Entendre la France (EF) collected contributions from participants on societal issues. In this article, we present a method for extracting and analyzing lexical networks derived from the text corpora formed by these contributions using the Semantic Atlas geometric model. The method permits to obtain (1) words and profiles shared by the three platforms, as well as words and profiles specific to each of them, (2) for each word, its lexical network. The list of words over-represented in these corpora and shared by the three platforms contains mainly words related to environmental issues and taxation. The lists specific to each of the platforms show distinct profiles. In particular, the GDN corpus shows an over-representation of words related to incivility and respect, as well as words related to environmental issues and the collective, the VD corpus shows an over-representation of terms related to political, governmental, or international organizations, political figures, personal, socio-economic contingencies, privileges, or modes of participation and voting. For EF, whose contributors are young (average age 29), one finds an over-representation of words related to discrimination, tolerance, and behaviours based on environmental concern. Finally, two examples of lexical networks extracted from the GDN corpus are detailed: that of the word transport (“transport”) and that of the word contre (“against”). For the word contre – chosen because its lexical network reveals which topics matter to the contributors – we show that the method makes explicit and synthesizes semantic links and reveals their organization. It can be seen from this example that environmental issues are an organizing center around which the main topics addressed by the contributors are articulated.